Tissue Engineering Scaffolds from La2O3 - Hydroxyapatite\Boron Glass Composites - (:unkn) unknown (SPRINGER, 2016)
Bioactive composites of bovine derived hydroxyapatite and boron containing bioactive glass were doped with 5, 10 and 15 wt.% lanthanum oxide (La2O3). Results showed that at low sintering temperatures (800 degrees C) the doping oxide of La2O3 promoted transformation to crystalline phases. Formation of secondary phases, such as rhenanite, NaCaPO4, and calcium silicate, Ca2SiO4, were also found. La was found to act as modifier and influenced the viscosity. The increase of La2O3 content led to decrease of pore size. Porosity amount 48.1 %, at 15-240 mu m size range were reduced, to 34.4 %, with 5-80 mu m size range and particle sizes of 0.3-6 mu m to 0.09-2 mu m, respectively. In addition to that compression strength (MPa) and microhardness (HV) of the performed composite bioceramics were in the range of 25 - 110 MPa, and 121 - 364 HV, respectively. Our investigations suggested that the porosity type has a strong influence on the compressive strength and microhardness properties of the final bioceramic products.
Keywords: Scaffolds; biocomposite; borate bioglass; biological hydroxyapatite; sintering; MECHANICAL-PROPERTIES; BHA; MICROSTRUCTURE; BEHAVIOR